Business Model for Sheep Fattening in Ethiopia - Bereket, Yemariam; Solomon, Rahel; Asnake, Woinshet; Ekule, Muluken; Wamatu, Jane; Kassie, Girma (International Center for Agricultural Research in the Dry Areas, 2023)
Sheep fattening is a practice that involves feeding and managing sheep for a specific time to increase their weight and improve their quality of meat production. In Ethiopia, particularly in rural areas, sheep fattening is a popular business venture among small-scale farmers. It provides an opportunity for farmers to generate income and improve their livelihoods. The practice is also important for meeting the increasing demand for meat in the country, which is expected to grow in the coming years due to population growth and urbanization. Sheep fattening business provides increased income for farmers, supplies consumers with high-quality meat, and contributes to the food supply chain. It also helps to meet the market demand for meat products and offers a livelihood for the different actors in the value chain. As a business, sheep fattening produces healthy and well-nourished animals that will fetch a higher price and generate more profit for the fattener. This type of business requires detailed planning of the production and marketing components of the business. This document presents a comprehensive business model for sheep fattening with rural entrepreneurs in mind. The model also presents the marketing strategy and the financial analysis of the model. The business model is developed by considering three locations in different parts of the country, namely, Bonga, Doyo Gena, and Menz. The document can however be used by any individual or group that is interested in sheep fattening. To have a profitable business, the entrepreneur needs to consider various factors such as the breed of the animals, the quality of feed and water, proper housing and sanitation, veterinary care, and market demand. It is important to select the right sheep breeds that are suitable for fattening and have good market value. The quality of feed and water provided to the animals is crucial for their growth and health. Proper housing and sanitation are necessary to prevent diseases and ensure the animals are comfortable. Regular veterinary care is also essential to prevent and cure any veterinary issues that may arise Finally, the entrepreneurs need to have a good understanding of the market demand for meat products and develop a marketing strategy to sell their products. With proper management, feeding, and care, the sheep fattening business can be a profitable and sustainable venture for rural entrepreneurs.